Partisipasi Masyarakat dalam Pengelolaan Pariwisata Berkelanjutan Desa Wisata Samiran, Kecamatan Kabupaten Boyolali - Baiquni, Muhammad; Aini, Itsna Nur (Sekolah Vokasi, Universitas Gadjah Mada, 2024)
Samiran Tourism Village has developed since 2009 based on community empowerment, so it is necessary to identify its management aspects to realize sustainable tourism. The research method is a qualitative approach through data collection of literature studies, observation, in-depth and semi-structured interviews. The interview informants were Samiran Tourism Village stakeholders who were determined by purposive sampling method tailored to the research objectives. Data analysis was conducted descriptively qualitatively through three steps of reduction, data presentation, and conclusion drawing. Samiran Tourism Village has achieved sustainable tourism management by involving various stakeholders but still placing the community as the main actor through the management structure and framework, stakeholder involvement, and management of change. The level of participation was identified through 5 stages. The high category level is at the implementation stage of enjoying results, and reporting because the community is fully involved in it, while the moderate level of participation is at the decision-making and evaluation stages, where the community still plays a role but is not independent / cooperates with other stakeholders. The factors that determine the level of participation can be divided into two, internal and external. Internal factors that influence are gender, social position, length of stay, and local hero, while external factors are influenced by policies made by the government, so that it is beyond the authority of the tourist village and cannot be controlled.